History of thyroidectomy in Ecuador - PACHECO-OJEDA, luis (2020)
Thyroid diseases were already known by the Chinese and Hindu civilizations two thousand years before the Christian era. Nevertheless, thyroid surgery was initially described only in Middle Age during the Byzantine Empire. Since then, an impressive development has occurred until nowadays. We have reviewed the most important facts of thyroid surgery development in the world and in Ecuador through the leading surgeons and their academic contributions. Goiter was the fundamental indication for surgery in the first centuries of this study. However, in the last decades, thyroid cancer has emerged as the main object of concern in this area. A steady increase in thyroid malignancies incidence has occurred in Ecuador and in many countries around the world. For this reason, current medical literature has become extensive in this matter.